2008
DOI: 10.1021/jp805671h
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure and Adsorption Geometry of l-Histidine on Cu(110)

Abstract: The adsorption of L-histidine on clean and oxygen-covered Cu(110) surfaces has been studied by soft X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. The valence band spectra, carbon, nitrogen and oxygen 1 s XPS and N K edge absorption spectra were measured for submonolayer, monolayer, and multilayer films. The spectra provide a detailed picture of the electronic structure and adsorption geometry at each coverage. In the monolayer, the histidine molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 24 publications
11
68
0
Order By: Relevance
“…In addition, the availability of a tunable X-ray source offers the possibility to perform also edge spectroscopies, in particular Near Edge X-ray Absorption Fine Structure (NEXAFS). Providing significant information on the molecular bonds orientation, this technique is very helpful for the characterisation of the structural conformation of the adsorbed molecules [44][45][46].…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the availability of a tunable X-ray source offers the possibility to perform also edge spectroscopies, in particular Near Edge X-ray Absorption Fine Structure (NEXAFS). Providing significant information on the molecular bonds orientation, this technique is very helpful for the characterisation of the structural conformation of the adsorbed molecules [44][45][46].…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…A few years later, Feyer et al [46] revisited the same system by HR-XPS and NEXAFS, investigating a wider range of temperatures. They concluded that, at high coverage (~1.5 ML), the IM side chains of the histidine molecules are randomly oriented.…”
Section: Histidinementioning
confidence: 99%
“…It has been indeed shown for glycine, alanine, leucine, lysine, histidine, to cite a few, on Cu(110) 6,7,20,22,[31][32][33] . Note the particular example of proline, which has an N atom in the pyrrolidine rings and binds to the Cu(110) surface via the oxygen atoms of the deprotonated carboxylate group and also via the N atom of the ring, thus confirming the affinity of both oxygen and nitrogen with copper.…”
Section: Discussionmentioning
confidence: 95%
“…From these well documented studies, it appears that amino acids mostly undergo a deprotonation of their acid groups when interacting with copper 4,12,13,20,21 ; they bind to the surface via the oxygen atoms of the carboxylate groups. Not similarly, such a deprotonation process is not systematic on gold; the latter metal seems also to favour an interaction of the NH 2 group with the metal, inducing a well detectable electronic transfer from the N atom to the metal; the latter is evidenced by a shift of the XPS N1s peak at Binding Energy (BE) below 399.5 eV 17,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…11,16,17 Recently, Prince et al used X-ray photoelectron spectroscopy (XPS) to determine the electronic structure of histidine on a Cu(110) surface as a function of coverage. 10 At low coverage, they found that the carboxyl group in the glycine part and the imino (N2) nitrogen atom in the imidazole ring were both bound to the Cu(110) surface. Prompted by these findings, in the present work we used Core-level photoelectron spectroscopy (CLPES) to examine the adsorption structure of histidine on a semiconducting surface (Ge(100)), both to compare the observed behavior with the findings of Prince et al for histidine on a Cu(110) surface and to clarify the variation of electronic structure for histidine adsorbed on a Ge(100) surface as functions of coverage and annealing temperature.…”
Section: Introductionmentioning
confidence: 99%